IDDF2018-ABS-0110 Efficacy and safety of SOFOSBUVIR/VELPATASVIR plus RIBAVIRIN for 12 or 24 weeks in genotype 1 or 2 HCV-INFECTED japanese patients with prior treatment failure to daa-based regimens. (June 2018) - Izumi, Namiki; Takehara, Tetsuo; Chayama, Kazuaki; Yatsuhashi, Hiroshi; Takaguchi, Koichi; Ide, Tatsuya; Kurosaki, Masayuki; Ueno, Yoshiyuki; Toyoda, Hidenori; Kakizaki, Satoru; Tanaka, Yasuhito; Kawakami, Yoshiiku; et al.
Abstract : Background: There is a growing number of Japanese patients with HCV infection who have failed direct acting antiviral (DAA)-based regimens and currently have no salvage therapies available. This Phase 3 study evaluates the efficacy and safety of sofosbuvir/velpatasvir (SOF/VEL) plus ribavirin (RBV) for 12 or 24 weeks in Japanese patients with genotype (GT) 1 or 2 HCV infection who have been previously treated with DAAs. Methods: Approximately 110 subjects were randomised 1:1 to receive SOF/VEL+RBV for 12 or 24 weeks. Randomization was stratified by GT and presence of cirrhosis. All subjects must have been previously treated with a DAA for at least 4 weeks. Subjects with GT1 HCV infection must have previously been treated with an NS5A inhibitor. The primary efficacy analysis is a comparison of the SVR12 rates for GT1 patients in each of the two treatment groups to a historical control SVR of 50%. Results: Of 117 patients enrolled, 45% were male, 81% had GT1 HCV infection, and 33% had cirrhosis. 84% had previously been treated with at least 2 different DAAs.86% of GT1 patients had previously been treated with daclatasvir plus asunaprevir and 91% of GT2 patients with SOF. Virologic outcomes at post-treatment week 4 are presented in the table below. There were no on-treatment virologic failures. Complete SVR12 and virology data will be presented. Three (3%) patients discontinued study drugs due to adverse events (AEs). One patient in the 12 week arm discontinued study drugs on Day 4 due to rash (related to study drugs). Two patients in the 24 week arm discontinued study drugs; one on Day 85 due to hepatic angiosarcoma (not related) and one on Day 57 due to depression (related). The two latter patients achieved SVR12. No Grade 3 or 4 AEs were considered related to study drugs (table 1). Conclusions: SOF/VEL+RBV has the potential to be a safe, well-tolerated, and effective treatment for Japanese patients with and without cirrhosis who have previously failed DAA-based regimens, a group without currently approved retreatment options. Baseline NS5A RASs did not affect treatment outcome.